P15 A well-designed multidisciplinary difficult airway management skills and drills difficult airway programme for ENT, anaesthesiology, peri-operative and ENT nurses. (3rd November 2019) - Choynowski, Michelle; Thornton, Mona; Contreras, Maya; Young, Orla; Malherb, Karen; Byrne, Dara
Abstract : Background: Simulation-based training is an excellent modality to practice complex airway emergencies while avoiding any harm to patients and can be used to improve the technical and non- technical skills required for difficult airway management. It is most effective when used to train teams that include all disciplines involved in the care of these patients as human factors issues, including poor communication and teamwork, contribute to adverse outcomes in up to 40% of difficult airway cases. 1 Summary of work: A collaborative multidisciplinary airway simulation programme was developed by a multidisciplinary team that included ENT, Anaesthesia, Perioperative Nursing Departments and the Irish Centre for Applied Patient Safety and Simulation (ICAPSS). A two-part programme was developed that focused on addressing the learning needs of all disciplines. The first part was three complex airway scenarios completed by teams of four learners comprised of ENT and anaesthesia doctors and nurses. The second part was a technical skills workshop supported by subject matter expert feedback. Skills included were cricothyroidotomy, percutaneous tracheostomy, fibreoptic intubation, high-flow nasal oxygen therapy and rigid bronchoscopy. All disciplines attended and participated in both parts of the programme. Summary of results: Post-workshop evaluation was overwhelmingly positive. All participants (n = 17) agreed or strongly agreed that the workshop improved their ability to use skills related to the topic and that the knowledge and skills that they learned will be useful to them in their job. All participants agreed that the workshop was enjoyable and that it addressed their learning needs. Discussion: The multidisciplinary team simulation programme specifically highlighted individual team member roles in managing difficult airways by including members for each discipline in every part of the programme. The inclusion of both medical and nursing staff to the practical workshop equally upskilled all members in respect to airway management to ensure a better understanding of equipment and procedures and ultimately benefiting all in the event of a challenging scenario. Conclusion: Using multidisciplinary team simulation programmes is a well-received method to teach collaborative management of complex airway scenarios in a team setting. Recommendations: The success of the programme highlights the need and the acceptability of this type of high impact training and how involving a multidisciplinary team at the development stage ensures buy-in and participation. The developers plan to deliver the programme more frequently to maintain team skills in managing difficult airway cases in a collaborative team setting. Reference: Cook T, et al. 4th National Audit Project of The Royal College of Anaesthetists and The Difficult Airway Society. Major complications of airway management in the United Kingdom, Report and Findings. Royal College of Anaesthetists . London, 2011